A case of vitiligo cured with cucumber and sulfur. (11th February 2019) - Liu, Zhigang; Wang, Ru; Zhang, Chaohui; Guo, Shanshan; Chen, Peijie
Abstract : This study investigates a 42‐year‐old man who used sulfur powder adhered to cucumber slices to successfully self‐treat a vitiligo condition. The treatment has resulted in no recurrence of the disease for 21 years. We analyzed the mechanism of this folk prescription for vitiligo, concluding that the success of the self‐treatment may be mainly associated with hydrogen sulfide (H2 S). The antibacterial activity of pentathionic acid (H2 S5 O6 ) and the antioxidant activity of cucumber might also play a role in the treatment.